Associations of -374T/A polymorphism of receptor for advanced glycation end products (RAGE) gene in Turkish diabetic and non-diabetic patients with coronary artery disease - (:unkn) unknown (International Institute of Anticancer Research, 2009)
Background: In this study we aimed to determine the possible risks for the development of coronary artery disease (CAD) in diabetic (DM+) and non-diabetic (DM-) patients according to he -374T/A polymorphism of the receptor for advanced glycation end products (RAGE) gene which affects the function of RAGE itself. Materials and Methods: This study was carried out in 52 non-diabetic and 62 diabetic patients with CAD, and 55 CAD-free, healthy volunteers as controls. The A-T transversion polymorphism at position -374 in the promoter region of the RAGE gene was analyzed by polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP) techniques. Results: The -374T/A AA genotype frequency was statistically higher in the whole patient group when compared with the control group (p=0.034), and statistically higher in the DM+ group when compared with the control group (p=0.003). Homozygosity for the -374A allele was found to be higher, but not statistically meaningful, in DM- patients (17.3%) when compared with the control group (13.2%). In this study, in contrast with other studies, we found possesion of the A allele to be an independent risk factor in CAD in patients with diabetes mellitus. Conclusion: Possesion of the -374A allele may contribute to the CAD in diabetic patients with triggering macrophages by increased levels of AGEs.
Keywords: Coronary artery disease; Diabetes mellitus; Genetics; Polymorphism; RAGE